2013
DOI: 10.1371/journal.pone.0083294
|View full text |Cite
|
Sign up to set email alerts
|

microRNA 126 Inhibits the Transition of Endothelial Progenitor Cells to Mesenchymal Cells via the PIK3R2-PI3K/Akt Signalling Pathway

Abstract: AimsEndothelial progenitor cells (EPCs) are capable of proliferating and differentiating into mature endothelial cells, and they have been considered as potential candidates for coronary heart disease therapy. However, the transition of EPCs to mesenchymal cells is not fully understood. This study aimed to explore the role of microRNA 126 (miR-126) in the endothelial-to-mesenchymal transition (EndMT) induced by transforming growth factor beta 1 (TGFβ1). Methods and ResultsEndMT of rat bone marrow-derived EPCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 34 publications
3
73
1
Order By: Relevance
“…Over stimulation of endothelial cells with VEGF leads to hyperactivity of the receptor (VEGFR 2 ). In cancer cells, (15,21,40). While SPRED-1 inhibits the activation of MAPK signaling, PIK 3 R 2 is associated with the inhibition of VEGF/PI3K/ AKT signaling (15,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over stimulation of endothelial cells with VEGF leads to hyperactivity of the receptor (VEGFR 2 ). In cancer cells, (15,21,40). While SPRED-1 inhibits the activation of MAPK signaling, PIK 3 R 2 is associated with the inhibition of VEGF/PI3K/ AKT signaling (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, molecules altering the expression of PIK 3 R 2 may be an effective way to lower the malignancy of cancer types. Several previous reports have demonstrated that miR-126 reduces the expression of PIK 3 R 2 by directly targeting its 3'-untranslated region (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…*P<0.05; **P<0.01; ***P<0.001 (one-way ANOVA followed by Bonferroni post-tests). MicroRNAs are involved in EndMT (Bijkerk et al, 2012;Fang and Davies, 2012;Ghosh et al, 2012;Kumarswamy et al, 2012;Zhang et al, 2013) and fibroproliferative diseases (Thum et al, 2008;van Rooij et al, 2008;Kato et al, 2009;Chung et al, 2010) by targeting genes that are crucial for endothelial homeostasis or activating fibroblasts. However, the role of microRNAs that are lost during EndMT and fibroproliferative diseases remains elusive.…”
Section: (B-e) Light Microscopy Images Of Endothelial Cells (B) Untrmentioning
confidence: 99%
“…It has previously been shown to have pleiotropic effects during EC differentiation and its genetic absence is known to augment vascular permeability (22,31). A potential mechanism by which miR-126 may decrease vascular permeability includes its targeted inhibition of PIK3R2 (32). PIK3R2 suppresses AKT signaling (32,33), which has been shown to play a critical role in modulating cytoskeletal rearrangement and maintaining barrier integrity (34).…”
Section: Ctce Decreased Lps-induced Pulmonary Vascular Leak and Inflamentioning
confidence: 99%
“…A potential mechanism by which miR-126 may decrease vascular permeability includes its targeted inhibition of PIK3R2 (32). PIK3R2 suppresses AKT signaling (32,33), which has been shown to play a critical role in modulating cytoskeletal rearrangement and maintaining barrier integrity (34). Thus, increases in miR-126 levels may be expected to augment AKT signaling and enhance vascular barrier integrity while its absence would generate the Figure 5.…”
Section: Ctce Decreased Lps-induced Pulmonary Vascular Leak and Inflamentioning
confidence: 99%